1995
DOI: 10.1038/ng0995-17
|View full text |Cite
|
Sign up to set email alerts
|

The developmental pattern of Brca1 expression implies a role in differentiation of the breast and other tissues

Abstract: We have examined the developmental expression of the murine breast and ovarian cancer susceptibility gene, Brca1, to investigate its role in the control of cell growth and differentiation. Specifically, we have analysed Brca1 expression during embryonic development, in adult tissues, and during postnatal mammary gland development, particularly in response to ovarian hormones. Our results suggest that Brca1 is expressed in rapidly proliferating cell types undergoing differentiation. In the mammary gland, Brca1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
242
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(270 citation statements)
references
References 22 publications
26
242
2
Order By: Relevance
“…The human BRCA1 gene encodes an 1863 amino acid nuclear protein that is expressed in a wide variety of adult human tissues (Marquis et al, 1995). Evidence implicates a role for BRCA1 in the control gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The human BRCA1 gene encodes an 1863 amino acid nuclear protein that is expressed in a wide variety of adult human tissues (Marquis et al, 1995). Evidence implicates a role for BRCA1 in the control gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The expression pattern of BRCA1 in the mouse has suggested that this gene plays a role in proliferation and di erentiation of a wide variety of tissues, and particularly that of the breast (Lane et al, 1995;Marquis et al, 1995). BRCA1 expression is also increased in proliferating cells (Gudas et al, 1996;Marks et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These two hypotheses, which are not mutually exclusive, stress that BRCA1 may have an important role in cellular di erentiation and proliferation. Direct evidence for an essential role of BRCA1 in mammalian development has been obtained from transgenic mice, since homozygous disruption of the BRCA1 gene results in embryonic lethality (Hakem et al, 1996), and the progressive changes of BRCA1 expression during mouse embryogenesis also imply a role for BRCA1 in the di erentiation process (Marquis et al, 1995). Alteration of the BRCA1 mRNA level has been observed in sporadic breast cancers, microdissections of biopsies from sporadic invasive breast tumors have shown a decrease in BRCA1 expression in the tumoral component of the samples (Thompson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%